Racism, Trauma and Empowerment in Selected Works of Afro-American fiction - Halířová, Kristýna (Univerzita Pardubice, 2024)
The aim of this bachelor thesis is to identify, depict, analyse and compare selected themes and issues found in Alice Walker's The Colour Purple and Toni Morrison's The Bluest Eye. The first two chapters of the paper, with the support of secondary sources, provide definitions of selected terms and an introduction to the historical-cultural background, focusing on the life of African Americans in the first half of the twentieth century. The three main chapters provide a detailed analysis of the identified themes and issues, such as racism, trauma, sexual abuse and narrative aspects, supported by primary literature and secondary sources and a final comparison of the said themes.
Rasismus, trauma a emancipace ve vybraných dílech afroamerické beletrie
Keywords: rasismus; sexuální zneužívání; trauma; Afroameričané; Walkerová, Alice; Morrisonová, Toni; racism; sexual abuse; trauma; African Americans; Walker, Alice; Morrison, Toni